Experiences of and attitudes to lifestyle modification for the management of multiple sclerosis: A qualitative analysis of free‐text survey data - Sandra L. Neate; Angela Donald; George A. Jelinek; Nupur Nag (Wiley, 2022)
Abstract Background Growing evidence suggests a role of lifestyle modification in improved health outcomes for people with multiple sclerosis (pwMS); however, perspectives of pwMS who engage in lifestyle modification are lacking. Objective We explored perspectives of pwMS regarding the modification of lifestyle‐related risk factors in multiple sclerosis (MS) for disease management to understand attitudes to and experiences of lifestyle modification as part of self‐management from a patient perspective. Design Participants were ≥18 years and English speaking who responded to a free‐text open‐ended question in the Health Outcomes and Lifestyle In a Sample of pwMS (HOLISM), an international online survey. Responses were analysed utilizing inductive thematic analysis. Results Under the exploration of lifestyle modification, themes describing the experiences and attitudes of participants included practical challenges and physical and psychological barriers, enablers of change and experienced outcomes. Although participants reported some practical and psychological challenges to adoption and maintenance of lifestyle behaviours, many expressed an ability to gain control of MS through engagement with lifestyle behaviours and the development of hope and optimism that accompanied this sense of control, at times leading to a sense of personal transformation. Conclusion Findings highlight the challenges experienced by pwMS in adopting lifestyle modifications for disease management as well as the positive benefits from following healthy lifestyle behaviours. Our findings may form the basis of more focussed qualitative explorations of the experiences and outcomes of lifestyle modification in MS in the future. Patient Contribution Consenting pwMS completed a survey capturing data on demographics, clinical course, lifestyle behaviours and health outcomes.